Effect Of Hydrocolloids And Storage On Physicochemical, Phenolic And Antioxidant Properties Of Sea Buckthorn Squash (Applied Biological Research, 2020)
The influence of three hydrocolloids namely xanthan gum, pectin, and guar  gum at concentrations of 1.5% were studied to assess the cloud stability of sea  buckthorn squash. The prepared squash was subjected to physicochemical,  phenolic, antioxidant and sensory evaluation at 0, 30, 60 and 90 days of  storage. In general, there was an increase in TSS, reducing and total sugars  while decrease in acidity, ascorbic acid, carotenoids, phenolic compounds and  antioxidant activity was observed in prepared sea buckthorn squash than  pulp. During storage, sea buckthorn squash showed increase in acidity, TSS,  reducing and total sugars in all the treatments. The squash containing pectin  showed the high ascorbic acid content and squash containing guar gum  showed high carotenoid contents at the end of storage period. The prepared  squash treated with pectin and guar gumshowed slight decrease in antioxidant  activity while as high loss of antioxidant activity was observed in xanthan gum  treatment at the end of storage. A declining trend was also observed in  phenolic compounds in all the treatments during storage. HPLC analysis  revealed that three phenolic compounds were present in pulp which was  significantly (p
Keywords: Antioxidants; ascorbic acid; HPLC; reducing sugars; sea buckthorn